Isolated Asymptomatic Short Sternum in a Healthy Young Girl. (20th July 2014) - Turturro, Francesco; Calderaro, Cosma; Montanaro, Antonello; Labianca, Luca; Argento, Giuseppe; Ferretti, Andrea
Abstract : Congenital sternal defects are rare deformities frequently associated with other anomalies of the chest wall and other organ systems. Although pectus excavatum, pectus carinatum, and cleft sternum can present as isolated deformity, in most cases they are associated with heart and inner organs anomalies and described as symptoms of syndromes like Marfan syndrome, Noonan syndrome, Poland anomaly, and Cantrell pentalogy. In contrast, the etiology of an isolated defect is not well understood. We observed a short sternum (dysmorphic manubrium, hypoplastic body, and complete absence of the xiphoid process) in a completely asymptomatic 13-year-old woman. A comprehensive instrumental exams panel was performed to exclude associated anomalies of the heart and of the other organ systems. The patient was completely asymptomatic and she did not need any medical or surgical treatment. To our knowledge, this is the first case of isolated short sternum reported in literature.